Teacher Preparation and Language Policy Appropriation: A Qualitative Investigation of Teach For America Teachers in Arizona - Amy J Heineke; Quanna Cameron (Arizona State University, 2013)
In this qualitative study, we examined teachers' language policy appropriation in the English-only state of Arizona. Specifically, we investigated teachers who received their professional placement and preparation through the Teach For America organization. We conducted the research in 2010 and 2011, a period when Arizona state language policy required that English learners be placed in English language development classrooms, separated from mainstream classrooms, to receive four hours of daily skill-based language instruction in language-specific content only, including grammar, vocabulary, reading, writing, and conversation. Through analysis of interview data from seven current corps members and eight alumni teachers, we investigated whether and how professional preparation shaped teachers' identity and agency to implement prescriptive linguistic and instructional mandates in the classroom.